2018
DOI: 10.1155/2018/5702103
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3: A Novel Mediator in Cardiovascular Disease

Abstract: Cardiovascular disease is a major cause of death worldwide. Inflammasome infiltration has been identified to play a central role in the pathological progression of certain cardiovascular diseases, such as vascular damage spanning atherosclerosis, aneurysm, or arteritis; ischemic heart disease; and other nonischemic heart diseases including diabetic cardiomyopathy, chronic heart failure, and hypertension- or virus-induced cardiac dysfunction. The NLRP3 inflammasome, a key participant in the innate immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 60 publications
3
102
0
1
Order By: Relevance
“…Multiple molecular mechanisms have been proposed to result in the development of DCM including myocardial inflammation, fibrosis, cardiomyocyte oxidative stress, apoptosis, autophagy, mitochondrial dysfunction and so on [4]. In addition, the NOD-like receptor 3 (NLRP3) inflammasome-induced pyroptosis, a novel programmed cell death process, is increasingly recognized in cardiovascular disease including DCM [5]. Caspase1 is activated by ligands of NLRP3 inflammasome, which further triggers the cleavage of pro-inflammatory cytokinesis such as interleukin-1β, 18 (IL-1β, and gasdermin D (GSDMD).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple molecular mechanisms have been proposed to result in the development of DCM including myocardial inflammation, fibrosis, cardiomyocyte oxidative stress, apoptosis, autophagy, mitochondrial dysfunction and so on [4]. In addition, the NOD-like receptor 3 (NLRP3) inflammasome-induced pyroptosis, a novel programmed cell death process, is increasingly recognized in cardiovascular disease including DCM [5]. Caspase1 is activated by ligands of NLRP3 inflammasome, which further triggers the cleavage of pro-inflammatory cytokinesis such as interleukin-1β, 18 (IL-1β, and gasdermin D (GSDMD).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting against the assembly and activity of the NLRP3 inflammasome is a potential and novel therapy for inflammasome-associated diseases, especially for cardiovascular diseases [55][56][57][58][59][60]. Some studies have indicated that blocking S194 phosphorylation can prevent NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…IL, interleukin; IFN, interferon; NO, nitric oxide; TLR, toll-like receptors; TNF, tumor necrosis factor; ROS, reactive oxygen species; mt-DNA, mitochondrial DNA; mt-ROS, mitochondrial reactive oxygen species Therapies associ ated with blocking the NLRP3 inflammasome have yielded promising results. An example of this, as previously mentioned, is the glyburide analog, 16673-34-0, that has shown benefits in ischemia-reperfusion animal models [63,64,98]. Although no clinical trials are being conducted to target NLRP3 directly, IL-1β, a byproduct resulting from NLRP3 activation, has revealed beneficial outcomes associated to inflammation resolution in both HFrEF and HFpEF.…”
Section: The Heart As a Target Of Systemic Inflammationmentioning
confidence: 99%